Removal of malachite green dye from contaminated aqueous solutions using WO3/Eu2O3-visible-light-assisted photocatalysis. Issue 10 (9th August 2021) - Abd-Rabboh, Hisham S.M.; Marzouki, Riadh; Alassaf, Abdulaziz; Loghbi, Mohamed; Hamdy, Mohamed S.
ABSTRACT: Aqueous solutions contaminated with malachite green (MG) organic water-soluble dye were treated with a series of novel europium oxide-doped tungsten oxide photocatalysts (WO3 /Eu2 O3 ) under visible light illumination. First, the photocatalyst series was prepared via a simple preparation procedure. Second, the produced photocatalyst series was investigated using different physical characterisation techniques, including: XRD, FTIR, FESEM, EDX and diffuse reflectance (DR). Characterisation results confirmed the successful and homogeneous doping of europium oxide particles within tungsten oxide. As a result, the photocatalytic activity of the synthesised Eu-doped WO3 samples was assessed at 425 nm. Finally, malachite green contaminated aqueous samples were treated with both un-doped- and doped-tungsten oxide photocatalysts under visible light illumination. Results indicate that doping of tungsten oxide with just 1 mole% europium oxide enhanced the photocatalytic activity of the doped-tungsten oxide, compared with the un-doped photocatalyst, by 4 folds, from 10% to 40%, with a slight decrease in the photocatalysts band-gap energies from 2.76 to 2.65 eV. The first-order rate constants for the photocatalysis of malachite green dye using samples W1-W4 were calculated to be 0.13, 0.61, 0.55, and 0.5, respectively.